Bioactivity of boronic acid derivative homodimers - Kaori Ota; Jian-Rong Zhou; Kazumi Yokomizo; Tomohiro Kozako; Shin-ichiro Honda; Nobuhiro Kashige; Makoto Furutachi; Kunihiro Sumoto (Results in Chemistry, 2022)
Homodimers that deployed boronic acids and their esters in their termini, namely boronic acid derivative homodimers, were designed. The boronic acid pinacol ester homodimer displayed antiviral activity and the boronic acid homodimer, in contrast, exerted cytotoxicity. Chemical modification of the boronic acid pinacol ester homodimers revealed that most of their derivatives showed an antiviral tendency as did their lead compounds albeit the same or worse antiviral activity. In contrast, chemical modification of the boronic acid homodimer revealed that most of its derivatives unexpectedly showed antibacterial and antiviral tendencies unlike their lead compound. The boronic acid homodimer also exerted antiproliferative activity against leukemic cell lines. The results of this study provided an insight into hitherto-unprecedented boronic acid and its pinacol ester homodimers as bioactive agents.